The Influence of Service Quality on Customer Trust Through Loyalty - Mariyatul Qibtiyana; Hapzi Ali (Siber International Journal of Sport Education, 2023)
This study aims to examine the effect of service quality on customer satisfaction and how satisfaction plays a role in fostering customer loyalty. Using qualitative methods and literature review, this study explores various relevant scientific articles in the field of marketing management. The results show that good service quality has a significant impact on customer satisfaction. In turn, customer satisfaction has a positive impact on customer loyalty. Satisfied customers tend to continue using a company's products or services and are more likely to recommend them to others. Therefore, customer satisfaction serves as an important measure of a company's service success. Based on these findings, this study emphasizes the importance of improving service quality to improve customer satisfaction.